One people, one destiny’: integrated selves and ‘Kinships’ of nations in the East African Community’s and founding member states’ anthems - Spemba Elias Spemba; Eliah Sibonike Mwaifuge (Taylor & Francis group, 2025)
Despite the unification of East African states to form the East African Community, the member states also aspire to grow as integrated selves within the unification. This article draws on African philosophy’s Ubuntu and Benedict Anderson’s (2016) ideas of imagined communities to investigate whether the East African Community’s anthem and those of its three member states enmesh the concepts of individual nations’ self-integration and communal aspirations with the community’s insistence on ‘oneness’. A close reading of Uganda’s, Tanzania’s, and Kenya’s anthems reveals that they symbolically represent individual member states as integrated selves and aspire to fortify communal relations with neighbouring states, thereby signalling that individual states will flourish amongst others—the very things addressed in the EAC’s anthem. Anthems’ fictitious worlds metaphorically shed light on the materialisation of a healthy East African Community and the growth of individual member states, grounded in the principles of self- and communal integration. The paper argues that the EAC’s anthems embody the philosophy of unity and, at the same time, convey the idea of unification among the member states.
Keywords: east african community; national anthems; ubuntu; oneness; imagined communities